Short- and long-term incidence of thromboembolic events in Takotsubo Syndrome as compared with acute coronary syndrome - El-Battrawy, Ibrahim; Gietzen, Thorsten; Lang, Siegfried; Ansari, Uzair; Behnes, Michael; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Angiology, 2019)
Thromboembolic events are a common complication in Takotsubo syndrome (TTS). However, their long-term incidence compared with acute coronary syndrome (ACS) is lacking. In-hospital and long-term incidence of thromboembolic events of 138 consecutive patients with TTS were compared with 138 sex- and age-matched patients with ACS. Predictors of events were analyzed. The incidence of thromboembolic events in TTS was 2-fold higher than ACS (21% vs 9%; P < .01) over a mean follow-up of 5 years. Although the left ventricular ejection fraction (LVEF) at event was significantly lower in TTS compared with ACS (38% [9%] vs 54% [11%]; P < .01), the follow-up LVEF was comparable. Patients with TTS suffering from thromboembolic events were more often treated with anticoagulation compared with ACS (44.8% vs 8.3%, P = .03). However, more patients presenting with ACS (100% vs 48.3%; P < .01) were discharged on aspirin. Only elevated C-reactive protein was a predictor of thromboembolic events using multivariate analysis (hazard ratio 1.1, 95% confidence interval, 1.0-1.2; P < .01). In conclusion, the risk of thromboembolic events in TTS was significantly higher than the risk of thromboembolic events in ACS over a mean follow-up of 5 years.
Gesehen am 05.11.2019